2003
DOI: 10.1155/s1565363303000086
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Cu(II)with His‐Val‐Gly‐Asp and of Zn(II)with His‐Val‐His, Two Peptides at the Active Site ofCu,Zn‐Superoxide Dismutase

Abstract: His-Val-His and His-Val-Gly-Asp are two naturally occurring peptide sequences, present at the active site of Cu,Zn-superoxide dismutase (Cu,Zn-SOD). We have already studied the interaction of His-Val-His=A (copper binding site) with Cu(II) and of His-Val-Gly-Asp=B (zinc binding site) with Zn(II). As a continuation of this work and for comparison purposes we have also studied the interaction of Zn(II) with His-Val-His and Cu(II) with His-Val-Gly-Asp using both potentiometric and spectroscopic methods (visible, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…The results obtained for the metal complexes of the non-protected peptide, HisValHis, have already been published from our laboratories and the data indicated that the ligand is a strong chelating agent for both copper(II) and zinc(II) [12,13]. The metal ion speciation of the copper(II)-Ac-HisValHis-NH 2 system is shown in Fig.…”
Section: Metal Complexes Of Ac-hisvalhis-nhmentioning
confidence: 79%
See 1 more Smart Citation
“…The results obtained for the metal complexes of the non-protected peptide, HisValHis, have already been published from our laboratories and the data indicated that the ligand is a strong chelating agent for both copper(II) and zinc(II) [12,13]. The metal ion speciation of the copper(II)-Ac-HisValHis-NH 2 system is shown in Fig.…”
Section: Metal Complexes Of Ac-hisvalhis-nhmentioning
confidence: 79%
“…Copper(II) and zinc(II) complexes of the non-protected forms of the peptides HisValHis and HisValGlyAsp were thoroughly studied in our laboratories and the results have been published recently [12,13]. These Inorganic Biochemistry studies reveal that both peptides have outstanding metal binding ability and versatile coordination chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the cleavage site between the positions 21 and 22 has been proposed [8]. Unfortunately, the protein used to prepare single crystals [25] lacks the whole N-terminal domain and starts only from 29 …”
Section: Resultsmentioning
confidence: 99%
“…The peptide has six readily available binding sites for zinc(II) ( [27][28][29]. However, the equilibrium constant of the process Zn 2+ + H 2 L = ZnH 2 L (log K = 6.58) is higher than the related value for histamine itself (log  101 = 5.15 [30]), or those of some {3N im } and {NH 2 ,2N im } coordinated complexes (log K = 5.1 [31] and 5.94 [29], respectively), indicating that additional binding sites should be taken into consideration. [12,34].…”
Section: Zinc(ii) Complexesmentioning
confidence: 99%
See 1 more Smart Citation